Manfaat Tehnologi Ditital Terhadap Motivasi Belajar Peserta Didik - muhasim, muhasim (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2017)
The development of digital technologies is the result of engineering intellect, mind and  human intelligence, which is reflected in the advancement of science, and provides benefits  in all aspects of human life. In the development of human communication has managed to bring a very rapid progression, from communication to manually change  into analog,  digital, where technology has provided ease in communicating quickly, without a limited  distance, space and time through the Internet. Based on the data of Internet users in Indonesia 2016 as much as 132.7 million people from a total population of Indonesia as much as 256.2 million people, certainly the year 2017 is much more rapid development. From the results of a survey by the Association of organizers of Internet network (JIHAD), revealed that, on average, through the Internet in Indonesia 67.2 million or 50.7 percent, to access via mobile devices and the computer. In West Nusa Tenggara as many as 3.3 million or 64 percent. The number of internet users from 80 per cent of whom are aged 15-19 years, meaning the teen age is still recorded as learners. Therefore the purpose of this paper is to find out how digital technology benefits against the motivation of learners. The method used is descriptive qualitative studies. As the analysis of data and information furnished observations, document definitions obtained from books written by experts and scripts through social media or the Internet. Discussion of the results obtained positive influence motivation towards learning digital technology learners. With a fixed geared to anticipate the negative influence posed that can disrupt moral behavior, and thus a threat motivation learning learners. Because energy must be given Faith, discipline on an ongoing basis, in order to take advantage of positive tehnolog digital to enhance learning motivation of learners.   Keywords: digital Technology, motivation of learning, learners